Tendencies of integration of the EAEU and the PRC within the framework of the project «One Belt, One Way» (Journal of Philosophy Culture and Political Science, 2018)
The Eurasian Economic Union (EAEU) from the idea of Eurasianism has turned into a political reality, becoming an integration association that has its place in international politics. Today, the countries of the EAEU and the People’s Republic of China (PRC) jointly implement the project «One Belt, One Way». The purpose of the research work is a political analysis of the specifics of the interconnection and problems of interaction between the EAEU countries and the PRC within the framework of the «One Belt, One Way» Project. The main directions and ideas of scientific research are the role of the creation and functioning of the EAEU, as well as the implementation of the project «One belt, one way» for the development of integration processes in Eurasia. ISSN 1563-0307 Journal. Philosophy series. Cultural science series. Political science series. №4 (62). 2017 231 Мұсатаев С.Ш. The scientific and practical significance of the work – the implementation of the project «One Belt, One Way» contributes to the diversified development of Europe and Asia, overcoming the global economic crisis. And also, gives a new impetus to the joint development of the EAEU and China, which are located on the same belt, on the Economic belt of the Silk Road. The theoretical and practical significance of the political study of these problems is beyond doubt. The research methodology is based on system, comparative, content and event analyzes. Results and results of the study: problems of interconnection and interaction between the Unified Energy System and the PRC within the framework of the «One Belt, One Way» project were studied, shortcomings and their solutions were identified, which positively affects the development of modern Kazakhstan political science and economy, integration and social development in general. The value of the research – contributes to the development of integration processes on the expanses of Eurasia.Key words: EAEU, the project «One belt, one way», the Economic belt of the Silk way, integration.